(untitled) (PANGEEA, 2025)
Geomorphological features - the premise of spatial organization in the S-E Ampoi Valley. Case Study: Alba Iulia The Geomorphological Characteristics Prerequisite of the Space Organisation in the South-East Part of the Ampoi Valley. Study of Research: Alba Iulia Town. The relief as an essential element in the organization of the space is an active constituent of which development is being reflected through a series of geographical changes under the incidence of a concurrence of elements. The geomorphologic hazards rendered evident in the urban and periurban space of the town join particularly in the category of gravitational and torential processes. The second, the third and the fourth rungs are affected. These hazards are decreasing the potentiality of utilization these phenomena. It would be very useful to elaborate some maps with the natural risks in order to correlate these problems with the future orientations regarding the extensions of the town.